Importance of inflation rate, income, interest rate and rate of return towards the profit performance of Takaful / Nadhilah Mahmood - Mahmood, Nadhilah (2011)
Takaful is an alternative form of financial instrument to insure assets, liabilities and other personal interests of individuals and organizations. The takaful industry in Malaysia is relatively a new industry as compared to its conventional counterparts. The research aims to identify the factors that influence the profit performance of takaful. Using time series data over the period 1990 until 2009, the findings of the study indicate that among the four variables studied, the income is the most significant factor that contributes to the profit performance of takaful. Other factors such as inflation rate, interest rate and rate of return do not appear significantly manipulate takaful purchase